The Effect of Selected Financial Ratios on Profitability: An Empirical Analysis of Listed Firms of Cement Sector in Saudi Arabia (Quarterly Journal of Econometrics Research, 2015)
The plinth emergence of infrastructures sector in the Kingdom of Saudi Arabia cardinally hinges upon the growth and development of the Cement industry. The Saudi cement industry is most cost competitive in the world due to availability of raw material and Fuel at very low prices by the government. This has encouraged the researchers to analyze the relationship between profitability and selected financial ratios of cement industry in Saudi Arabia. The research paper makes an endeavor to determine the profitability of listed cement companies in Saudi Arabia with five years accounting period from 2008 to 2012. The paper encompasses six variables, namely, Debt to Equity Ratio (DER), Inventory Turnover Ratio (ITR), Debtors’ Turnover Ratio (DTR), Creditors’ Velocity (CRSV), Total Assets Turnover Ratio (TATR) and Net profit Margin (NPM). Profitability as a dependent variable is exhibited by Net profit Margin (NPM) while the selected ratios DER, ITR, DTR, CRSV, TATR and CRSV are expressed as independent variables. Based on the findings of the study, it is cogently revealed that there is a significant relationship between the three selected ratios and Net Profit Margin (NPM) of cement companies in Saudi Arabia.